Picosecond time-resolved fluorescent spectroscopy of 1-anilino-8-naphthalene sulfonate binding with staphylococcal nuclease in the native and molten globule states - Gao, G.; Y. Li; Wang, W.; Zhong, D.; S. Wang; Gong, Q. (J Photochem Photobiol BJ Photochem Photobiol BJ Photochem Photobiol B, 2015)
We studied the picosecond time-resolved fluorescent spectroscopy of 1-anilino-8-naphthalene sulfonate (ANS), which binds to the staphylococcal nuclease (SNase) of the wild-type (WT) and the molten globule (MG) state. Three ANS emission bands at approximately 530nm, approximately 495nm, and approximately 475nm are resolved, corresponding to three ANS states: the free ANS in solution and associated form adsorbing to surface sites and binding to active sites. The surface hydrophobicity of the WT is moderate and different from the MG state, as shown both in the position of the bands and by the concentration dependent ANS fluorescent decay. For MG, the decay of two blue bands accelerated with the increment of the ANS concentration, whereas the WT did not show this dependency. However, when pdTp, an inhibitor, was attached to the active site of the MG state, band 2 decay was also independent of the ANS concentration. These results indicate that the protein hydrophobic sites have two types of interactions with ANS.